Dissolving microneedles for transdermal drug delivery - Chua, Jinyu (2018)
Dissolving microneedles are considered as one of the most promising methods for transdermal drug delivery. However, the polymer and sugar materials used for fabrication generally have weaker mechanical properties as compared to insoluble metal or silicon. In other biomedical applications, nanoclay is incorporated into polymers to improve their mechanical properties. This has not yet been investigated in the field of dissolving microneedles. In this study, polymer-clay composite microneedles are fabricated by simple solvent casting from poly (lactic-co-glycolic acid) (PLGA) and bentonite, a non-toxic and biodegradable nanoclay. The effects of bentonite on the mechanical and in-vitro dissolution properties of the microneedles are investigated. PLGA microneedles were fabricated with 0, 5, 10 and 20wt.%-bentonite at molar concentration of 400mg/ml of organic solvent. With increasing bentonite amount used, fracture force significantly increased with bentonite incorporation. Fracture force of 5wt.% is 0.0189N per needle, 3 times larger than 0.0057N of 0wt.%. This reinforcement effect of bentonite suggests that sufficient dispersion of bentonite in PLGA was achieved, despite higher degree of clay aggregates observed. Dissolution rate decreases with increasing bentonite amount used. 5wt.% microneedle patches have a 50% slower dissolution rate as compared to 0wt.% microneedle patches. In conclusion, PLGA-bentonite composite dissolving microneedles were successfully fabricated via the method of solution blending and solvent casting at room temperature. In future studies, nanoclay can be used as a viable modifier to improve mechanically weaker polymers and control rapidly dissolving polymers used for microneedle fabrication.